Perencanaan Ulang Struktur Jembatan Way Magnay di Ruas Jalan Krui-Biha Kabupaten Pesisir Barat - susanto, susanto; Isneini, Mohd; Husni, Hasti Riakara; Bayzoni, Bayzoni (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2023)
AbstractWay Magnay Bridge is a reinforced concrete bridge span 2 x 25 m as liaison between Krui – Biha Regency West Coast . Way magnay bridge have width 6.42 m with traffic lane width 4.5 m. Base the load used in redesign of this bridge is SNI 1725-2016 and load earthquake use SNI regulations 2833-2016. Based on calculations that have been done , obtained reinforcement plate floor vehicle use flexural reinforcement D16 – 75 mm whereas reinforcement for used D10 – 295 mm. Girder transverse obtained main reinforcement 4D25 and reinforcement shear Ø10 -350 mm. Girder elongated obtained flexural reinforcement 20D34, reinforcement press 8D32, shear reinforcement Ø22 – 150 mm and shrink reinforcement 4D29. for pile cap abutments obtained flexural reinforcement direction x D25 – 130 mm, flexural reinforcement y direction D25 – 150 mm, shear reinforcement direction x Ø19 – 130 mm and shrink reinforcement D22 – 150 mm, Rim obtained flexural reinforcement D32 – 80 mm and shrink reinforcement D25 – 90 mm, Back wall obtained flexural reinforcement D22 – 200 mm and shrink reinforcement D22 – 85 mm, meanwhile for Foundation pole stake obtained main reinforcement 4D13 and shear spiral reinforcement Ø12 – 50 mm with total 10 piles Keywords : Redesign bridge , Reinforced concrete bridge , Way Magnay